Leadership: Theory, Principle and Style - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2018)
This art icle explains recent theoret ical development s n the study of organizat ional leadership. It begins with a concise overview of the meaning and concept of leadership in terms of research, theory, and pract ice. This article suggests that success is certain if the application of the leadership styles, principles and methods is properly and fully applied in management because quality of leadership tradition offers great opportunity to further educational leadership and management policies and pract ices by accept ing and utilizing the basic principles and styles of leadership. Academic Voices Vol.6 2016: 11-20